2002
DOI: 10.1207/s15327655jchn1903_04
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Evaluation of the Perceptions of Health of Elders of Different Multicultural Backgrounds

Abstract: The purpose of this study was to discover the perceptions of health and the health maintenance practices of 4 different cultural and ethnic groups. Interviews were conducted at senior citizen centers in and around a large metropolitan center in Texas. Five Native Americans, 44 African Americans, 32 Latinos, and 13 Vietnamese were questioned about their views on being healthy. Huff and Kline's Cultural Assessment Framework was used to analyze the responses. Functionality and independence were dominant themes no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…A number of potential, specific mechanisms have been implicated in this respect. One possibility is that individuals from different ethnic groups may take different dimensions of health into account when rating their health (Hakim & Wegmann, 2002;Krause & Jay, 1994). For instance, a qualitative study comparing African Americans', Hispanic Americans', and Caucasian Americans' thoughts when rating their health showed that although Caucasians were thinking about general physical functioning, African Americans and Hispanics were more likely to consider health problems (Krause & Jay, 1994).…”
Section: Ethnic Background and Self-rated Healthmentioning
confidence: 99%
“…A number of potential, specific mechanisms have been implicated in this respect. One possibility is that individuals from different ethnic groups may take different dimensions of health into account when rating their health (Hakim & Wegmann, 2002;Krause & Jay, 1994). For instance, a qualitative study comparing African Americans', Hispanic Americans', and Caucasian Americans' thoughts when rating their health showed that although Caucasians were thinking about general physical functioning, African Americans and Hispanics were more likely to consider health problems (Krause & Jay, 1994).…”
Section: Ethnic Background and Self-rated Healthmentioning
confidence: 99%
“…[20] The health care provider must also recognize that food preferences, environmental factors like sanitation, habits, and educational-behavioral practices influence individuals' perceptions of health and illness. The most important, according to Hakim and Wegman, [21] is the "client's perception of health, since this perception drives the client's response to care" (p. 162).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…[18,19] Filipinos believe that evil spirits can cause an individual to be sick. As reported in Traditional Filipino Health Practices, [21] the evil spirit ("manga ga mud") may cast a spell on a disliked person by obtaining personal items such as a piece of cloth, a piece of hair, pictures, or a piece of jewelry. Food poisoning is also believed to be the doings of the evil spirits.…”
Section: Description Of a Person That Is Not Healthymentioning
confidence: 99%
“…Scholars have identified many of the pervasive health and disability related disparities that exist within the LGBT community (e.g., Fredriksen-Goldsen et al, 2012; Fredriksen-Goldsen, Emlet, et al, 2013; Lick et al, 2013), however they have not yet adequately addressed some of the psychosocial experiences of LGBTPWD. If cultural belief systems have the potential to influence how one attributes meaning to their own understanding of subjective health (Hakim & Wegmann, 2002), it is imperative that rehabilitation scholars and practitioners understand how socially diverse groups perceive and construct their own characterizations of health. Understanding the conceptual features of health from an emic worldview perspective (i.e., within a specific cultural group) could help scholars and practitioners enhance their cultural competencies with LGBTPWD (Sue & Sue, 2008).…”
Section: Current Studymentioning
confidence: 99%